Muslimat NU Program in Improving Economic Empowerment of Jayasakti Village Community Anak Tuha Central Lampung - Wulandari, Silvi; Soimah, Soimah (Episteme: Jurnal Kajian Mahasiswa, 2025)
Muslimat NU is a women's organization under the auspices of Nahdlatul Ulama (NU), functioning as an autonomous body. Led by Muslim women, this organization aims to foster individuals and communities that are devout, intelligent, morally upright, and capable of leading peaceful, just, and prosperous lives. This study aims to analyze the empowerment of women through the Muslimat Nahdlatul Ulama (NU) organization in Kampung Jayasakti, Anak Tuha, Lampung Tengah. The focus of the research is on the role of Muslimat NU in supporting women's empowerment in economic and socio-religious fields, the supporting and inhibiting factors influencing the empowerment process, as well as the impacts on the community. The approach employed in this study is qualitative, using data collection techniques such as in-depth interviews, direct observation, and documentation. The findings indicate that the programs implemented by Muslimat NU play a significant role in enhancing economic empowerment, self-awareness, capacity, and participation of women in various socio-economic and religious activities. The success of this empowerment is supported by the organization's economic stability and the commitment of religious leaders and administrators. However, challenges remain in implementing these programs, including a lack of program innovation and member participation. The study concludes that women's economic empowerment through Muslimat NU in Kampung Jayasakti contributes to improving the independence and quality of life of the community. Therefore, Muslimat NU administrators must continue to innovate in enhancing empowerment strategies, while encouraging the community to be more actively involved in supporting the programs implemented.